Some aspects of the mineralogy of the Kibi Bauxite (Journal of Science and Technology, 2016)
The mineralogy of the Kibi bauxite was investigated using XRD, IR and Thermoanalytical methods. Five pit samples were used in the study. Results indicated that the gibbsite, boehmite and geothite minerals are present in a well crystallised state as coarse dispersions. The aluminium substitution in the geothite lattice was high, varying between 20-29 mol per cent. It can therefore be predicted that aluminium recovery at low temperature digestion conditions will be low and the aluminium content of the geothite will remain undigested under such conditions.